Peran Agama Islam terhadap Kesehatan Mental menurut Zakiah Daradjat - Assyifa Noor Izzah Tanjung; Cucu Setiwan (Gunung Djati Conference Series, 2022)
This study aims to discuss the role of Islam on mental health according to Zakiah Daradjat. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion in this study indicate that mental health aims to develop and use as much as possible all existing potential, skills, and qualities to create happiness for oneself and others, and avoid mental disorders and diseases. According to Zakiah Daradjat, one of the tastes of religion is therapy (healing) for mental disorders. Practicing religion in daily life protects people from mental disorders and can also restore the mental health of anxious people. This study concludes that religion has a role in mental health problems. This study recommends to various parties to be more concerned about mental health, where religion is a supporting factor in solving mental health problems.